ANALISIS BESAR KESALAHAN MAGNITUDE FUNGSI RESPON FREKUENSI HASIL PENGUJIAN DENGAN METODE EKSITASI KEJUT AKIBAT KETERBATASAN PANJANG WAKTU REKAM - Partogi, Agusmian; Abidin, Zainal; Bagiasna, Komang (Mesin, 2006)
This paper describes the mathematical analysis concerning the influence of time record length on the magnitude error of the Frequency Response Function (FRF) using impact hammer testing. In this paper, the value of damped natural frequency is assumed to be the same with the value of positive integer multiple of the frequency resolution in response spectrum. The mathematical analysis results an equation which can be used to calculate the error value of FRF magnitude due to the finite time record length. As an illustrative example, the simulated FRF using impact hammer testing on four S-DOF vibration system models is presented in this paper. The simulation is performed using a computer program which is constructed using MATLAB software. The simulation results show that the error of FRF magnitude obtained from the simulated testing is almost the same with the error value derived from theoritical equation.